La prochaine génération de téléphonie mobile (5G) et ses implications (Infrastructure, Réglementation) - Edward M. Roche; Benjamin H. Dickens-Jr.; Walker Townes (Netcom)
The “5G” is a new generation of wireless telecommunications technology that promises to revolutionize how the world communicates. Everything from autonomous vehicles, robots conducting delicate surgery, virtual and augmented reality devices, drones, the “Internet of Things” (IoT), and generally all mobile communications will be enabled by a new tranche of bandwidth between 6-Ghz and 300-Ghz, some of it licensed, but much of it not. But 5G is diﬀerent. For the ﬁrst time, the physical infrastructure will be separated from the logical or “virtual” infrastructure. Software Deﬁned Networks (SDN) will be set up and torn down, grown and lessened according to demand.Complex network management will be done by Machine Learning (ML) and Artiﬁcial Intelligence (AI). But for all of this to work properly, major carriers will need to accept international standards and open up their interfaces to outsiders, even to competitors. This is where the regulatory and legal ﬁght will take place. Unless suﬃcient attention is paid now to these emerging issues, users dependent on advanced telecommunications in both North American and the European Union will be prevented from enjoying the full range of beneﬁts promised by 5G, and as a consequence innovation will lag behind other regions of the world.